Profile of hospitalizations due to mental and behavioral disorders in Brazil (REMUNOM, 2025)
Mental and behavioral disorders are a public health problem that grows every year, being considered the evil of the century. Thus, the present work aims to describe the profile of hospitalizations due to Mental and Behavioral Disorders in Brazil from 2019 to 2024. The work in question consists of a retrospective, descriptive, quantitative study of hospitalizations that occurred in the country, through the Hospital Information System of the Unified Health System (SIH/SUS), made available by the SUS Information Technology Department (DATASUS). According to the data analyzed, 1,141,443 hospitalizations were recorded in the period analyzed. It can be seen that hospitalizations for schizophrenia, schizotypal and delusional disorders were predominant with 30% of the records, the majority of cases were in the southeast region of the country with 446,733 hospitalizations (39.13%). There was a predominance of hospitalizations in the age group corresponding to 30 to 39 years. Regarding the type of care, the majority were emergency, with higher rates in 2023, with a predominance of males. Thus, the present study achieved its objective and promoted the discussion of fundamental data, since knowledge of the profile of hospitalizations for mental disorders in the country is essential for research and planning of health services, aiming to identify the risk profile for the development of such disorders, in order to promote effective and qualified care.